KARAKTERISTIK SISTEM HIDROGEOLOGI KARS DENGAN ANALISIS HIDROKIMIA ION UTAMA DI DAERAH CIJULANG, CIAMIS, JAWA BARAT - SETIAWAN , TAAT
The objective of this research is to identify the karst hydrogeological system by using hydrochemical analysis of major elements in Cijulang area, Ciamis, West Java. This research is conducted by using remote sensing analysis and hidrogeological method, mainly hydrochemical analysis. Stratigraphycally, the research area lies at Limestone Member of Pamutuan Formation that consists of calcarenite with calcilutite and calcareous claystone alternation. Geological structures are dominated by morphological lineaments and fractures. Regional hydrogeological system is controlled by fractures with north-south, northwest-southeast, and west-east orientations. The karst spring emerging mechanism is mostly controlled by impermeable layers of calcareous claystone that form contact free draining spring. At the elevation ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â± 20 masl lies permanent karst springs with high discharge. The emergence of those springs are controlled by lithological contacts with calcareous claystone and alluvial deposits that form dammed and contact free draining spring. Hydrochemical characteristics of karst spring have temperature range of 23.9-28 derajat C (hypothermal spring), hardness 155-266 mg/l CaCO3 (hard water), electric conductivity 350-597 ?S/Sm (fresh groundwater), total dissolved solid 200-329 mg/l and pH 7.15-8.15. The most abundant major elements are Ca2+ (38.593.61 mg/l), Mg2+ (5.06-41.3 mg/l) and HCO3-(182-353 mg/l). The Pco2 ranges 0.159 %-2.572% and generally saturated with respect to CaCO3 (SIcalcite > 0).Groundwater are commonly Ca-Mg-HCO3 and Mg-Ca-HCO3 facies indicates the water interaction with limestone and calcareous claystone. The zones of karst hydrogeology are divided into dry zone, transition zone, andcontinuous water circulation zone. The dry zone lies above the transition zone, at various elevation following the topographic pattern. The transition zone lies at 100-35 masl. At the elevation of 110-65 masl, karst springs are formed by diffusion flow through the fractures system. In dry season, karst spring have minimum discharge (< 1 l/s). Decreasing of Pco2 indicates that the system has no continuous CO2 supply that caused increasing of pH and SIcalcite. High lineaments density (6-9/km2) indicates intensiveness of the fractures system. At the elevation of 65-35 masl, water flows vertically passing the conduit system to the below of its zone. In dry season, karst springs have minimum discharge (<1l/s) and some of them have permanent discharge. Increasing of Pco2 indicates effective supply of CO2 that caused decreasing of pH and SIcalcite. The lower lineaments density than the upper zone (5-8/km2 ) shown that the water flows more concentrated than the upper zone. The elevation of 35-20 masl represents the continuous water circulation zone with permanent karst spring character. Continuous contact between water and CO2 makes Pco2 and pH relatively constant, and SIcalcite close to equilibrium condition. The characteristic of water flow is predominated by horizontal direction through conduit system which is accumulation from the upper zone and from the wider catchment area.